Tropical forest leaves may darken in response to climate change. Issue 12 (December 2018) - Doughty, Christopher; Santos-Andrade, Paul; Shenkin, Alexander; Goldsmith, Gregory; Bentley, Lisa; Blonder, Benjamin; Díaz, Sandra; Salinas, Norma; Enquist, Brian; Martin, Roberta; Asner, Gregory; Malhi, Yadvinder
Abstract Tropical forest leaf albedo (reflectance) greatly impacts how much energy the planet absorbs; however; little is known about how it might be impacted by climate change. Here, we measure leaf traits and leaf albedo at ten 1-ha plots along a 3, 200-m elevation gradient in Peru. Leaf mass per area (LMA) decreased with warmer temperatures along the elevation gradient; the distribution of LMA was positively skewed at all sites indicating a shift in LMA towards a warmer climate and future reduced tropical LMA. Reduced LMA was significantly (P < 0.0001) correlated with reduced leaf near-infrared (NIR) albedo; community-weighted mean NIR albedo significantly (P < 0.01) decreased as temperature increased. A potential future 2 °C increase in tropical temperatures could reduce lowland tropical leaf LMA by 6–7 g m− 2 (5–6%) and reduce leaf NIR albedo by 0.0015–0.002 units. Reduced NIR albedo means that leaves are darker and absorb more of the Sun's energy. Climate simulations indicate this increased absorbed energy will warm tropical forests more at high CO2 conditions with proportionately more energy going towards heating and less towards evapotranspiration and cloud formation. Tropical forest leaves are expected to absorb more of the Sun's energy with climate warming, which could further increase global temperatures.